Impak Perkahwinan Kanak-Kanak Terhadap Pemberdayaan Wanita dan Pendekatan Islam dalam Menanganinya: Child Marriage’s Impacts on Women’s Empowerment and Islamic Approaches to Resolving It - Abdol Malek, Muhammad Al-Ghazalli; Samuri, Mohd Al Adib (‘Abqari Journal, 2022)
Some religious parties justify contemporary child marriage based on the permissible ruling of marriage permitted in Islam, based on the marriage between the Prophet and Lady Aisha. Nowadays, child marriage has been regarded as a violation of child rights and is a key agenda in its claims of disinfection globally. International conventions such as the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) seek to curb marriage through the setting of the age of marriage, while the Convention on the Rights of the Child (CRC) stresses the importance of children as a priority in all matters relating to their welfare. This effort is in line with the Sustainable Development Goals (SDG) 2030 to strengthen women's rights. Nevertheless, child marriage is still in practice, causing the international community to urge legal reform to curb child marriage practices. This article uses a qualitative approach through literature review by analyzing primary and secondary documents through classical books and academic writing in journals. Studies have found a range of negative impacts that harm children from child marriage such as sexual exploitation, neglect of educational rights, mental and reproductive health risks, and domestic violence. This study acts as an enlightenment for the community to understand the harm caused by child marriage towards the girls, thus launching advocacy to ensure the success of the child marriage equality containment agenda in order to strengthen the empowerment of women's rights, through and Islamic approach in dealing with it. This awareness leads to the justification of the government and its stakeholders to act in line with the framework of Siyasa al-Shar'iyya to ensure the well-being (maslaha) of the girls. ABSTRAK Sesetengah agamawan menjustifikasi perkahwinan kanak-kanak kontemporari menurut hukum keharusan perkahwinan yang dibenarkan dalam agama Islam, berdasarkan perkahwinan antara Rasulullah SAW dan Aishah RA. Pada masa kini, perkahwinan kanak-kanak telah dianggap sebagai pelanggaran hak kanak-kanak dan menjadi agenda utama dalam tuntutan pembasmiannya di peringkat global. Konvensyen antarabangsa seperti Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) berusaha untuk membendung perkahwinan ini melalui penetapan had umur perkahwinan, manakala Convention on the Rights of the Child (CRC) pula menegaskan tentang kepentingan kanak-kanak sebagai keutamaan dalam segala hal berkaitan kepentingan mereka. Usaha ini selari dengan matlamat Sustainable Development Goals (SDG) 2030 bagi memperkasakan hak wanita. Namun, perkahwinan ini masih diamalkan sehingga menyebabkan komuniti antarabangsa menggesa pembaharuan undang-undang bagi membendung amalan perkahwinan kanak-kanak. Artikel ini menggunakan pendekatan kualitatif melalui kajian kepustakaan dengan menganalisis dokumen primer dan sekunder melalui bahan klasik dan penulisan akademik di dalam jurnal. Kajian mendapati pelbagai impak negatif yang memudaratkan kanak-kanak akibat perkahwinan kanak-kanak seperti eksploitasi seksual, pengabaian hak pendidikan, risiko kesihatan mental dan reproduktif serta keganasan rumah tangga. Kajian ini bertindak sebagai pencerahan kepada masyarakat untuk memahami kemudaratan terhadap kanak-kanak perempuan disebabkan perkahwinan kanak-kanak, sekali gus melancarkan advokasi bagi menjayakan agenda pembendungan perkahwinan kanak-kanak demi memperkasakan pemberdayaan wanita, melalui pendekatan Islam dalam menanganinya. Kesedaran ini membawa kepada kewajaran pemerintah dan pemegang taruh untuk bertindak selari dengan kerangka Siyasah al-Shar’iyyah bagi menjamin kemaslahatan kanak-kanak perempuan.